Post‐Transition State Bifurcation Controls Torsional Selectivity in Radical Addition of Allenes - Wu, Rong‐Kai; Zhang, Shuo‐Qing; Hong, Xin (Chemistry : a European journal, 2024)
Post‐transition state bifurcation (PTSB) has received wide attention in the field of reaction mechanism research due to its role in producing nonstatistical reaction selectivity, which cannot be solely explained by transition state theory. Particularly, even subtle molecular motions such as bond torsion can precipitate PTSB, thereby significantly complicating the quantitative understanding of dynamic selectivity. In this work, we found that the radical addition of allenes is an elementary transformation that generally exhibits PTSB stereoselectivity, where a single radical addition transition state can lead to both Z ‐ and E ‐allylic radicals via the post‐transition state allylic single bond torsion. Interestingly, dynamic Z / E ‐selectivity favors the Z ‐allylic radicals, which contrasts the thermodynamic preference. Based on the dynamics study of twenty‐five radical additions of mono‐substituted allenes with diverse electronic and steric effects, we have identified that this dynamic stereoselectivity is synergistically controlled by the transition state structure and the differential trends within specific dimensions of the bifurcating reaction coordinates, which also holds true for di‐substituted allene substrates. This study refines the mechanism of radical addition of allenes and underscores the importance of the differential trend of the reaction coordinates in controlling dynamic selectivity, offering a deeper insight into PTSB selectivity factors.